Studi Komparatif: Tinjauan Pelaksanaan Kurikulum Merdeka dalam Pembelajaran Sejarah di SMA - Bahroni, Agung; Zulkarnain, Zulkarnain (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
The "Merdeka Curriculum" has influenced the implementation of learning in schools. This research aims to examine the implementation of history education within the Merdeka Curriculum. The research method used is a literature study by analyzing previous research related to the topic. The research findings indicate that there are still many challenges in implementing the Merdeka Curriculum in history education. Teachers, as the primary facilitators of learning, lack a comprehensive understanding of the Merdeka Curriculum concept; they face limitations in developing interactive teaching methods and models; there is a shortage of supporting learning resources; and there is insufficient socialization, training, and mentoring in the implementation of history education within the Merdeka Curriculum.